Diversity of macrofungal genus Russula and Amanita in Hirpora Wildlife Sanctuary, Southern Kashmir Himalayas - SHAUKET AHMED PALA; ABDUL HAMID WANI; RIYAZ AHMAD MIR (Biodiversitas Journal of Biological Diversity, 2012)
Pala SA, Wani AH, Mir RA. 2012. Diversity of macrofungal genus Russula and Amanita in Hirpora Wildlife Sanctuary, Southern Kashmir Himalayas. Biodiversitas 13: 65-71. The Hirpora Wildlife Sanctuary that extends over an area of 114 km2 lies in the Pir Panjal range at a distance of 70 km in south-west of summer capital Srinagar. It is rich in biodiversity including macrofungal diversity. The Sanctuary has been subjected to high ecological and anthropogenic disturbance due to the construction of Mughal road which is major threat for its biodiversity. Since there is hardly any report of documentation of macrofungi from this sanctuary. In this back drop a survey was carried out during the year 2010 and 2011 to explore and invetorise macrofungal diversity of the sanctuary. During thesurvey a no of macrofungi were documented, among which Amanita and Russula were dominant genus represented by 7 species each. All the 14 species viz. Amanita ceciliae (Berk. & Broome) Bas. Amanita flavoconia G.F. Atk., Amanita muscaria var. formosa Pers., Amanita pantherina (Fr.) Krombh., Amanita phalloides (Fr.) Link., Amanita vaginata (Bull. ex Fr.) Vitt., Amanita virosa (Fr.) Bertillon, Russula aeruginea Fr., Russula atropurpurea (Krombh.) Britz., Russula aurea Pers., Russula cyanoxantha (Schaeff.) Fr., Russula delica Fr. Russula emetica (Schaeff. ex Fr.) Gray. and Russula nobilis Velen. are ectomycorrhizal in nature and among them Russula aeruginea Fr. is reported first time from the Kashmir.